Dampak Lingkungan Pemasaran Global terhadap Ekonomi Indonesia - Sefiani Dwi Azmi (PT. Anagata Sembagi Education, 2024)
The success of multinational corporations in the Indonesian market can be attributed to their adeptness in tailoring global marketing strategies to suit the Indonesian market, encompassing political, economic, socio-cultural, geographical, and economic factors. This research aims to explore the impact of the global marketing environment on the Indonesian economy. Employing a descriptive analysis method, which involves describing the results of problem analysis to address research questions, the study delves into global marketing challenges faced by Indonesian firms aiming to compete internationally. The findings of this study unveil strategies for Indonesian companies to navigate global marketing landscapes. Data collection is primarily conducted through library research methods. Global marketing initiatives can yield both positive and negative effects, contingent upon how domestic marketing adapts to them. The government plays a crucial role in steering the Indonesian economy towards global market competitiveness through its policies